Efektivitas teknik discrete trial training (DTT) dalam meningkatkan keterampilan berbahasa reseptif pada anak dengan autism spectrum disorder tingkat 1 - Aztaraneta Ewa Abbas; Sukma Noor Akbar; Rusdi Rusli (Universitas Muhammadiyah Malang, 2026)
This study examines the effectiveness of the Discrete Trial Training (DTT) technique in improving receptive language skills in children with level 1 autism spectrum disorder, who commonly experience challenges in understanding language. DTT involves breaking down skills into small, manageable steps and guiding children gradually until mastery is achieved. The study used a pre-experimental one-group pretest–posttest design with purposive sampling. Data were collected through assessments, observations, and interviews. The assessment instruments included the Children Autism Rating Scale (CARS) and the Assessment Instrument for the Development of Children with Special Needs The findings show that DTT significantly increased receptive language skills, as indicated by the Paired Sample t-test result with a significance value of 0.007, which is below the 0.05 threshold, leading to the acceptance of the alternative hypothesis. These results indicate that the DTT technique is effective in enhancing receptive language skills in children with level 1 autism spectrum disorder